P030 Animal production and risk of lympho-hematopoietic cancers in three cohort studies of farmers within the agricoh consortium-preliminary results. (1st September 2016) - El-Zaemey, Sonia; Schinasi, Leah; Ferro, Gilles; Baldi, Isabelle; Tual, Séverine; Lebailly, Pierre; Nordby, Karl-Christian; Kjaerheim, Kristina; Schüz, Joachim; Monnereau, Alain; Brouwer, Maartje; Kromhout, Hans; et al.
Abstract : Objectives: Animal farming entails a variety of exposures to infectious agents, endotoxins and pesticides, which may play a role in the aetiology of lympho-hematopoietic cancers. The aim of this investigation was to assess lymph-hematopoietic cancers risk in association with raising animals on farms. Method: Self–reported animal production (cattle, hogs, sheep/goats, poultry) were collected in the US Agricultural Health Study, French Agriculture and Cancer Study, and Cancer in the Norwegian Agricultural Population cohorts. Associations with risk of lymph-hematopoietic cancers, including 18 cancer outcomes, were evaluated using Cox proportional hazard models, adjusted for sex, pesticides and other confounders. The referent category consisted of farmers who didn't produce the animal species being evaluated. Cohort-specific hazard ratios (HR) were combined using random effects meta-analysis. Among 316, 270 farmers, 3, 282 lymph-hematopoietic cancers were diagnosed between 1993–2011. Results: 60%, 35%, 33%, and 27%, of farmers raised cattle, hogs, poultry and sheep/goats, respectively, although the prevalence varied by cohort. Raising cattle was not associated with overall non-Hodgkin lymphoma (meta-HR=1.04; 95% Confidence Interval (CI): 0.93–1.16; I2 = 13%), but was associated with follicular lymphoma (meta-HR = 1.43; 95% CI: 1.02–2.01; I2 = 21%). The risk of myelodysplastic syndromes was significantly reduced in farmers who raised sheep/goats (meta-HR = 0.66; 95% CI: 0.46–0.95; I2 = 0%), as was the risk of marginal-zone lymphoma among farmers who raised hogs (meta-HR = 0.57; 95% CI: 0.33–0.99; I2 = 0%), with the majority of exposed cases coming from two cohorts. We observed no meta-association between raising poultry and any lymph-hematopoietic cancer subtypes. It should be noted that differences in raising animals between countries and years might have influenced relevant exposures and therefore HR estimates for lymph-hematopoietic cancer sub-types might vary by cohort for specific animals. Conclusions: This study suggests specificity of associations between specific animals raised and lymph-hematopoietic cancer sub-types. These associations will be investigated further considering number of animals raised and farmers producing single species.